2008
DOI: 10.1007/s10509-008-9764-0
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent compressible convection with rotation—penetration above a convection zone

Abstract: We perform Large eddy simulations of turbulent compressible convection in stellar-type convection zones by solving the Naviér-Stokes equations in three dimensions. We estimate the extent of penetration into the stable layer above a stellar-type convection zone by varying the rotation rate (Ω), the inclination of the rotation vector (θ) and the relative stability (S) of the upper stable layer The computational domain is a rectangular box in an f-plane configuration and is divided into two regions of unstable an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Brummell et al [119] find that rotation decreases overshoot, while Dietrich and Wicht [130] find that only S affects overshoot and not rotation. Browning et al [121] studied 3D rotating core convection and found prolate penetration zones aligned with the rotation axis, which is consistent with the local box simulations of Pal et al [169] who found less penetration at the equator than at the poles. The effects of magnetism are even less studied, but convection can pump magnetic fields out of the convection zone and into CBM regions; this process was discovered by Drobyshevski and Yuferev [170] and has been observed in simulations [171,172]; magnetic pumping has been suggested as a mechanism for solar active region formation [173] and has been used to study the structure of the Sun's magnetic field below the convection zone [174].…”
Section: Rotational Constraint and Magnetic Pumpingsupporting
confidence: 64%
“…Brummell et al [119] find that rotation decreases overshoot, while Dietrich and Wicht [130] find that only S affects overshoot and not rotation. Browning et al [121] studied 3D rotating core convection and found prolate penetration zones aligned with the rotation axis, which is consistent with the local box simulations of Pal et al [169] who found less penetration at the equator than at the poles. The effects of magnetism are even less studied, but convection can pump magnetic fields out of the convection zone and into CBM regions; this process was discovered by Drobyshevski and Yuferev [170] and has been observed in simulations [171,172]; magnetic pumping has been suggested as a mechanism for solar active region formation [173] and has been used to study the structure of the Sun's magnetic field below the convection zone [174].…”
Section: Rotational Constraint and Magnetic Pumpingsupporting
confidence: 64%
“…Rotation has important effect on convection and overshooting. For example, penetration depth may vary with latitudes because the Coriolis effect differs at high and low latitudes (Browning et al 2004;Pal et al 2008). In certain circumstance, vortices might appear when the Rossby number is small (Käpylä et al 2011).…”
Section: Discussionmentioning
confidence: 99%